Speaking performance and anxiety levels of Chinese EFL learners in face-to-face and syncrhonous voice-based chat / Chen Yanqiu - Chen , Yanqiu (2018)
With the advanced development of mobile technology, there is a need for exploration of the potential of synchronous voice chats (SVC) operated within a mobile-assisted environment using mobile instant messaging apps, (e.g WhatsApp, WeChat, Messenger), within the language learning area (Cruz-Martinez, 2017). This is especially true in China, where language researchers and teachers have long been facing the challenge of finding effective approaches to develop language learners’ speaking performance. With an aim to address this problem, this study investigated the effectiveness of SVC in improving Chinese EFL (English as Foreign Language) learners’ speaking performance, as well as the impact of utilizing the mobile WeChat on anxiety levels. A mixed-mode research design was applied to provide a more complete picture. Forty second-year students in a public Chinese university participated in the experiment. Over a four week period, students participated in four chat sessions while completing four tasks using both face-to-face (F2F) and synchronous voice chat (SVC) modes. The quantitative data was collected by compiling the oral scores of participants’ performance of the tasks, as well as their responses to anxiety questionnaires. The qualitative data was then collected from a focused group interview. The data revealed a significant difference in learners’ speaking performance, with oral performances in SVC outperforming F2F chats. There was also a significant difference in anxiety levels in both chat modes: learners were found to experience higher levels of anxiety in F2F chat than in SVC.